Patient-Centred Care for Patients With Diabetes and HIV at a Public Tertiary Hospital in South Africa: An Ethnographic Study - Edna N. Bosire; Emily Mendenhall; Shane A. Norris; Jane Goudge (International Journal of Health Policy and Management, 2021)
BackgroundHealthcare systems across the globe are adopting patient-centred care (PCC) approach to empower patients in taking charge of their illnesses and improve the quality of care. Although models of patient‐centredness vary, respecting the needs and preferences of individuals receiving care is important. South Africa has implemented an integrated chronic disease management (ICDM) which has PCC component. The ICDM aims to empower chronic care patients to play an active role in disease management process, whilst simultaneously intervening at a community/ population and health service level. However, chronic care is still fragmented due to systemic challenges that have hindered the practice of PCC. In this article, we explore provider perspectives on PCC for patients with comorbid type 2 diabetes and HIV at a public tertiary hospital in urban South Africa. MethodsThis study utilizes ethnographic methods, encompassing clinical observations, and qualitative interviews with healthcare providers (n = 30). Interview recordings were transcribed verbatim and data were analyzed inductively using a grounded theory approach. ResultsProviders reported various ways in which they conceptualized and practiced PCC. However, structural challenges such as staff shortages, lack of guidelines for comorbid care, and fragmented care, and patient barriers such as poverty, language, and missed appointments, impeded the possibility of practicing PCC. ConclusionHealth systems could be strengthened by: (i) ensuring appropriate multidisciplinary guidelines for managing comorbidities exist, are known, and available, (ii) strengthening primary healthcare (PHC) clinics by ensuring access to necessary resources that will facilitate successful integration and management of comorbid diabetes and HIV, (iii) training medical practitioners on PCC and structural competence, so as to better understand patients in their sociocultural contexts, and (iv) understanding patient challenges to effective care to improve attendance and adherence.